Pelatihan Pembangunan Website E-Commerce dalam Mengelola Hasil Karya Siswa/Siswi di SMKN 5 Batam - I Made Sondra Wijaya; Dely Indah Sari (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2021)
SMKN 5 Batam is a State Vocational High School in the city of Batam, although basically it is a public school that does not require publication of the school because it already has its own students, but it never hurts to keep updating student activities which can later be used as a medium for information on prospective parents of students who will prepare schools for prospective students. With advances in information technology that has been very advanced, one of them is by using the website, the needs related to activities carried out by students at SMKN 5 Batam.